Methsuximide for Intractable Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The use of methsuximide in 25 children with intractable epilepsy is reported from the Department of Neurology and School of Pharmacy, University of North Carolina, Chapel Hill.